1996
DOI: 10.1007/bf00626028
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional cancer therapy ?survey of patients with gynaecological malignancy

Abstract: Although the benefits remain unproven, a considerable number of cancer patients use unconventional therapy, in many cases without the knowledge of the oncologist. At the oncological out-patient department of the women's clinic of the Justus-Liebig-University Giessen we conducted a survey of the various unconventional methods used. 38.8% (80/206) of the patients used unconventional therapies, mainly mistletoe extracts (50%), trace minerals (46%), megavitamins (39%), and enzymes (22%). The perceived etiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The authors suggested that this may be due to patients resorting to non-conventional therapy when less hope of cure is given by the physicians. In contrast, other studies have demonstrated that CAM use is not associated with more advanced disease stage [29-31]. This may be related to the complexity of underlying psychological and behavioural mechanisms influencing the use of CAM in cancer patients such as attitude, family support and coping behaviour as have been shown by previous reports [32,33].…”
Section: Discussionmentioning
confidence: 83%
“…The authors suggested that this may be due to patients resorting to non-conventional therapy when less hope of cure is given by the physicians. In contrast, other studies have demonstrated that CAM use is not associated with more advanced disease stage [29-31]. This may be related to the complexity of underlying psychological and behavioural mechanisms influencing the use of CAM in cancer patients such as attitude, family support and coping behaviour as have been shown by previous reports [32,33].…”
Section: Discussionmentioning
confidence: 83%
“…At present, 38–60% of all cancer patients in Western industrialized countries take advantage of complementary and alternative medicine (CAM) during the course of their disease and to support their treatment [1]. In the case of breast cancer, the figure is even as high as 90% [2, 3]. Breast cancer patients and gynecological cancer patients in particular, are the group with the highest percentage usage of integrative methods [1, 4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Well-known examples of medical specialties in which CAM therapies are frequently used are oncology and obstetrics [1, 2]. In the past, medical schools tended to focus on the question of whether CAM should be taught to medical students at all, but the debate has now moved on to how much, which methods and when CAM should be taught [3, 4].…”
Section: Introductionmentioning
confidence: 99%